STING protects breast cancer cells from intrinsic and genotoxic-induced DNA instability via a non-canonical, cell-autonomous pathway - Cheradame, Laura; Guerrera, Ida Chiara; Gaston, Julie; Schmitt, Alain; Jung, Vincent; Goudin, Nicolas; Pouillard, Marion; Radosevic-Robin, Nina; Modesti, Mauro; Judde, Jean-Gabriel; Cairo, Stefano; Goffin, Vincent (Oncogene, 2021)
STING (Stimulator of Interferon Genes) is an endoplasmic reticulum-anchored adaptor of the innate immunity best known to trigger pro-inflammatory cytokine expression in response to pathogen infection. In cancer, this canonical pathway can be activated by intrinsic or drug-induced genomic instability, potentiating antitumor immune responses. Here we report that STING downregulation decreases cell survival and increases sensitivity to genotoxic treatment in a panel of breast cancer cell lines in a cell-autonomous manner. STING silencing impaired DNA Damage Response (53BP1) foci formation and increased DNA break accumulation. These newly identified properties were found to be independent of STING partner cGAS and of its canonical pro-inflammatory pathway. STING was shown to partially localize at the inner nuclear membrane in a variety of breast cancer cell models and clinical tumor samples. Interactomics analysis of nuclear STING identified several proteins of the DNA Damage Response, including the three proteins of the DNA-PK complex, further supporting a role of STING in the regulation of genomic stability. In breast and ovarian cancer patients that received adjuvant chemotherapy, high STING expression is associated with increased risk of relapse. In summary, this study highlights an alternative, non-canonical tumor-promoting role of STING that opposes its well-documented function in tumor immunosurveillance.